2013
DOI: 10.1104/pp.112.212514
|View full text |Cite
|
Sign up to set email alerts
|

Oleosin of Subcellular Lipid Droplets Evolved in Green Algae    

Abstract: In primitive and higher plants, intracellular storage lipid droplets (LDs) of triacylglycerols are stabilized with a surface layer of phospholipids and oleosin. In chlorophytes (green algae), a protein termed major lipid-droplet protein (MLDP) rather than oleosin on LDs was recently reported. We explored whether MLDP was present directly on algal LDs and whether algae had oleosin genes and oleosins. Immunofluorescence microscopy revealed that MLDP in the chlorophyte Chlamydomonas reinhardtii was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 34 publications
2
70
0
Order By: Relevance
“…After omitting these likely redundant sequences, we retained 800 to 850 DNA-deduced oleosin sequences (Supplemental Table S1) for all subsequent analyses. Our extensive searches confirmed what our laboratory had reported earlier (Huang et al, 2013b): that organisms other than plants and their ancestor green algae do not possess oleosin genes.…”
supporting
confidence: 77%
“…After omitting these likely redundant sequences, we retained 800 to 850 DNA-deduced oleosin sequences (Supplemental Table S1) for all subsequent analyses. Our extensive searches confirmed what our laboratory had reported earlier (Huang et al, 2013b): that organisms other than plants and their ancestor green algae do not possess oleosin genes.…”
supporting
confidence: 77%
“…In earlier work, we found that proteolysis of CGP destabilizes bC-plastoglobuli, suggesting that CGP may have a similar role to fibrillins in stabilizing the plastoglobules (Katz et al, 1995;Youssef et al, 2010;Singh and McNellis 2011). We did not identify in our proteomes homologs of green algal oleosins (Huang et al, 2013), Chlorella spp. caleosin (Lin et al, 2012), Nannochloropsis spp.…”
Section: Sequence Analysis and Comparisons With Other Gene Familiesmentioning
confidence: 45%
“…Here, we report that C. reinhardtii MLDP polyclonal antibody (Huang et al, 2013) recognizes and cross-react with the S. quadricauda MLDP, indicating the presence and conservation of MLDP-like protein in green microalga linage (Figure 1). Additionally, we also tested the relative abundance of MLDP in two important stress conditions like nitrogen starvation and salt stress condition; confocal imaging reveals the accumulation of MLDP in both the stress condition (Figure 1).…”
Section: Detection Of Mldp During Abiotic Stress-immunostainingmentioning
confidence: 99%